A review of eight unusual pediatric skin and soft-tissue lesions: Diagnosis, workup, and treatment. Issue 12 (December 2015) - Argenta, Anne E.; Chen, Wendy; Davis, Amy; Losee, Joseph E.; Davit, Alexander; Grunwaldt, Lorelei
Summary: The spectrum of clinical presentations in pediatric skin and soft-tissue lesions often makes diagnosis challenging. Delays in diagnosis and subsequent treatment can be life threatening, and they can subject patients to more complicated reconstruction. This retrospective case series reviews the presentation, management, and current literature on eight pediatric skin and soft-tissue lesions. For rare lesions and those with unclear pathology, a multidisciplinary approach is strongly advocated for optimal management.